Unveiling the Therapeutic Targets and Active Components of Xianlinggubao Capsule in Osteoarthritis and Osteoporosis through Network Pharmacology and Bioinformatic Analysis - Ma, Quanji; Ma, Xuhui; Hua, Xuejiao; Liu, Jianhui (Current Pharmaceutical Design, 2025)
<span class=
Keywords: osteoarthritis